PRELIMINARY STUDY ON ADDITIVELY MANUFACTURED PLASTIC LINER OF AN ACETABULAR CUP COMPONENT (Jurnal Teknologi (Sciences & Engineering), 2022)
Additive manufacturing is extensively used in the medical field due to its flexibility in manufacturing implants based on the patient’s requirements. This research study aims to investigate the additively manufactured plastic liner part, which is one of the parts of an artificial hip joint. In this study, fused deposition modeling (FDM) is used for fabricating the plastic liner from polylactic acid (PLA). The investigation was carried out to understand the manufacturability of dimensionally accurate, defect-free and better surface quality of the additively manufactured cup liner and to study the wear behaviour of the material chosen. The dimensions of the formed components were measured using a coordinate measuring machine (CMM). Non-destructive testing methods namely dye penetrant and radiography were carried out for identifying the existence of any surface or internal defects, respectively. The surface roughness values were measured to characterize the surface texture of the component made. The wear behaviour of the PLA material was studied by a pin-on-disc test. It is seen from the macrostructural images that some external surface defects exist. These observations are also confirmed by the dye penetrant test results. However, no internal defects were noticed by the radiography testing of the additively manufactured liner. The surface roughness measurements and macrostructural images have shown the poor surface finish of the part. The coefficient of friction of 0.302 and higher specific wear rate of PLA material were observed in pin-on disc test.